Análisis del comportamiento dinámico y energético de un vehículo eléctrico híbrido en hev en operación en ruta con condiciones orográficas específicas - Dillon Granizo, José Luis (2025)
The growing global need to mitigate environmental risks and reduce dependence on fossil fuels has driven the automotive industry toward environmental sustainability and energy efficiency. This study analyzes the dynamic and energetic behavior of a Toyota Prius C hybrid electric vehicle under specific orographic conditions in the city of Ambato, Ecuador. A quantitative, experimental, and cross-sectional approach was adopted, using advanced monitoring devices for dynamic behavior data and geographic position information, allowing real-time data collection on speed, engine RPM, fuel consumption, battery charge state, and geolocation. Tests were conducted in two scenarios: an urban route with a 50 km/h speed limit and an interurban route with a 90 km/h limit, evaluating performance under different orographic and traffic conditions. The results show differentiated energy consumption patterns according to terrain slope and traffic conditions, providing valuable information to optimize the efficiency of hybrid vehicles in mountainous terrain.